2016
DOI: 10.1155/2016/9785467
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardia Associated with Steroid Use for Laryngeal Edema in an Adult: A Case Report and Literature Review

Abstract: Steroids are used for specific indications in the perioperative period to reduce laryngeal or spinal cord edema, or for prophylaxis and treatment of postoperative nausea and vomiting. Given the other potential causes for hemodynamic alterations in the perioperative setting, it is important for physicians to be aware of cardiovascular side effects of short term steroids. Changes in blood pressure and heart rate, cardiac dysrhythmias, and even death have been described in patients receiving short term intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…In most of the case reports, the patient either received IV dexamethasone [4,6] or IV methylprednisolone [4][5]7] or high dose oral prednisolone [8]. There is one study where sinus bradycardia was documented after oral methylprednisolone dose of 52 mg as well as with tapering dose of prednisone [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the case reports, the patient either received IV dexamethasone [4,6] or IV methylprednisolone [4][5]7] or high dose oral prednisolone [8]. There is one study where sinus bradycardia was documented after oral methylprednisolone dose of 52 mg as well as with tapering dose of prednisone [3].…”
Section: Discussionmentioning
confidence: 99%
“…There are few case reports over the years about the association of pulse dose corticosteroid therapy and cardiac arrhythmias especially sinus bradycardia [ 1 - 2 , 5 ]. In most of the case reports, the patient either received IV dexamethasone [ 4 , 6 ] or IV methylprednisolone [ 4 - 5 , 7 ] or high dose oral prednisolone [ 8 ]. There is one study where sinus bradycardia was documented after oral methylprednisolone dose of 52 mg as well as with tapering dose of prednisone [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…11,15,17,18 In a review of the literature by Stroeder et al, 19 93 cases of bradycardia attributed to PST have been reported, from 1970 to 2014. Other cases, not included in this work, have been reported 12-14,17,18 reaching a total amount of 105 cases of bradycardia consequently to corticosteroids administration (11 case reports, 6 case series, 2 prospective studies, and 1 retrospective study).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been described following short term oral prednisone use. Cardiac arrhythmias as a result of dexamethasone use have been less frequently described and primarily involve pediatric patients [4].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy was planned with Bortezomib along with VAD regimen. Bortezomib: 2 mg (day 1,4,8,11), Vincristine: 0.5 mg (day 1 to day 4), Dexamethasone: 30 mg (day 1 to day 4), Doxorubicin: 10 mg (day 1 to day 4). The patient had uneventful three cycles of chemotherapy.…”
mentioning
confidence: 99%